The impacts of environmental performance and propensity disclosure on financial performance: Empirical evidence from unbalanced panel data of heavy-pollution industries in China - Kai Chang (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: Environmental performance and propensity disclosure is important for stakeholders to estimate firms' incentives in environmental management practices. The purpose of this article is to explore the impacts of environmental performance and propensity disclosure on financial performance using unbalanced panel data of eight heavy-pollution industries in China. Design/methodology/approach: Environmental performance and propensity exhibits mutual causality relationship with Tobin's Q value using unit root and co-integration test of panel data. Using panel data analysis, we take the impacts of environmental performance and propensity disclosure on financial performance from 2008 to 2012. Findings: Environmental performance has a significantly negative impact on Tobin's Q value at the significance levels of 1 %, while environmental propensity has a significantly positive effect on Tobin's Q value at the significance levels of 5 %. Firm size, financial leverage and return of assets have significantly positive impacts on financial performance at the significance levels of 1 %. Meanwhile the effect of corporate environmental performance and propensity on financial performance has a significantly periodic difference from 2008 to 2012. Research limitations/implications: Those results are helpful for environmental regulators to evaluate the implementing effect of voluntary environmental policy and for firms' managers to increase market expectation and improve financial performance. Originality/value: Environmental performance is estimated by 30 environmental indicators in eight heavy-pollution industries in China. Environmental performance and propensity disclosure has a U-typed relationship with financial performance.
Keywords: 650; environmental performance; environmental preference; unbalanced panel data; Tobin's Q; causality test